2001
DOI: 10.1086/322630
|View full text |Cite
|
Sign up to set email alerts
|

Salivary Cytomegalovirus (CMV) Shedding, Glycoprotein B Genotype Distribution, and CMV Disease in Human Immunodeficiency Virus–Seropositive Patients

Abstract: To assess the frequency of shedding of cytomegalovirus (CMV) in saliva, the distribution of CMV glycoprotein B (gB) genotypes, and the occurrence of CMV diseases, we screened 98 human immunodeficiency virus (HIV)-seropositive patients without CMV disease. CMV was detected by culture more frequently in saliva (45 [46%] of 98 patients) than in blood (7 [7.5%] of 93) and was associated with CD4 cell counts <100 cells/mm3 (P=.013). CMV in the saliva of 37 patients was successfully genotyped. Three patients (8%) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
35
1
3

Year Published

2003
2003
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 19 publications
8
35
1
3
Order By: Relevance
“…A 4-to 26-fold-increased odds of HHV shedding in the saliva of HIV seropositive patients was observed. The frequencies of detection in the HIV-positive and HIV-negative groups are consistent with those previously reported, indicating that HHVs are frequently shed asymptomatically in the saliva of HIV-infected patients who take HAART (3,4,6,19,37,38,44,68). The higher prevalence in the HIV-positive group may reflect altered health status or differences in herpesvirus seropositivity between the groups, particularly for CMV.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…A 4-to 26-fold-increased odds of HHV shedding in the saliva of HIV seropositive patients was observed. The frequencies of detection in the HIV-positive and HIV-negative groups are consistent with those previously reported, indicating that HHVs are frequently shed asymptomatically in the saliva of HIV-infected patients who take HAART (3,4,6,19,37,38,44,68). The higher prevalence in the HIV-positive group may reflect altered health status or differences in herpesvirus seropositivity between the groups, particularly for CMV.…”
Section: Discussionsupporting
confidence: 88%
“…In prior studies of HIV-infected patients without KS or AIDS, the detection rates in saliva for HSV-1/HSV-2 were 24% (4,20), EBV, 71% to 93% (6,18,24,42,43), CMV, 17% to 77% (19,20,25,44), and HHV-8, 0% to 57% (3, 4, 11, 13, 36-38, 56, 68, 71). Most prior studies examined for individual HHVs in saliva, not their simultaneous presence, and oral lesions may have been present or not reported (44).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…However, recent evidence has demonstrated that mucosal shedding of HCMV occurs commonly in many healthy individuals (do Canto et al, 2000;Lucht et al, 1998;Shen et al, 1996) and very frequently in immunocompromised patients (Diamond et al, 2000;Fidouh-Houhou et al, 2001;Lucht et al, 1998;Mostad et al, 2000). In this study, RhCMV shedding was detected consistently in many animals, indicating low-level, persistent infection.…”
Section: The Pattern Of Rhcmv Detection Is Very Similar To What Is Knmentioning
confidence: 43%
“…Among AIDS patients, gB genotype distribution has been widely studied in blood, urine, semen, vitreous, and saliva specimens (1,4,9,12,18). However, the frequency distribution of gB genotypes in cerebrospinal fluid (CSF) specimens has not been studied yet.…”
mentioning
confidence: 99%